2020
DOI: 10.2478/raon-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of ultrasound-guided vacuum-assisted evacuation of large breast hematomas

Abstract: AbstractBackgroundBreast hematoma is an often underrated and disregarded post-procedural complication in the literature. Current treatment modalities are comprised of either surgical or expectant therapy, while percutaneous procedures play a smaller role in their treatment. We aimed to examine the efficacy of vacuum-assisted evacuation (VAE) in the treatment of clinically significant large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Indications for return to the operating room for evacuation of the hematoma include rapidly expanding size, threatened flap, hematomas in the head and neck that may compromise the airway, and hemodynamic instability. 24 26 28 Smaller, more stable hematomas may be amenable to evacuation at bedside. Historically, hematomas were evacuated surgically by reopening the surgical incision or making a small incision superior to the hematoma, and utilizing pressure, irrigation, and suction to evacuate the clot.…”
Section: Postoperative Fluid Collectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications for return to the operating room for evacuation of the hematoma include rapidly expanding size, threatened flap, hematomas in the head and neck that may compromise the airway, and hemodynamic instability. 24 26 28 Smaller, more stable hematomas may be amenable to evacuation at bedside. Historically, hematomas were evacuated surgically by reopening the surgical incision or making a small incision superior to the hematoma, and utilizing pressure, irrigation, and suction to evacuate the clot.…”
Section: Postoperative Fluid Collectionsmentioning
confidence: 99%
“…A 2020 study by Almasarweh et al found that ultrasound-guided vacuum-assisted evacuation of breast hematomas was a safe alternative to surgical evacuation, and was able to be performed effectively between days 1 and 597 postoperatively. 28…”
Section: Postoperative Fluid Collectionsmentioning
confidence: 99%